Measurement‐based care using DSM‐5 for opioid use disorder: can we make opioid medication treatment more effective?. (30th January 2019) - Marsden, John; Tai, Betty; Ali, Robert; Hu, Lian; Rush, A. John; Volkow, Nora
Abstract: Context and Purpose: Measurement‐based care (MBC) is an evidence‐based health‐care practice in which indicators of disease are tracked to inform clinical actions, provide feedback to patients and improve outcomes. The current opioid crisis in multiple countries provides a pressing rationale for adopting a basic MBC approach for opioid use disorder (OUD) using DSM‐5 to increase treatment retention and effectiveness. Proposal: To stimulate debate, we propose a basic MBC approach using the 11 symptoms of OUD (DSM‐5) to inform the delivery of medications for opioid use disorder (MOUD; including methadone, buprenorphine and naltrexone) and their evaluation in office‐based primary care and specialist clinics. Key features of a basic MBC approach for OUD using DSM‐5 are described, with an illustration of how clinical actions are guided and outcomes communicated. For core treatment tasks, we propose that craving and drug use response to MOUD should be assessed after 2 weeks, and OUD remission status should be evaluated at 3, 6 and 12 months (and exit from MOUD treatment) and beyond. Each of the 11 DSM‐5 symptoms of OUD should be discussed with the patient to develop a case formulation and guide selection of adjunctive psychological interventions, supplemented with information on substance use, and optionally extended with information from other clinical instruments. A patient‐reported outcome measure should be recorded and discussed at each remission assessment. Conclusions: MBC can be used to tailor and adapt MOUD treatment to increase engagement, retention and effectiveness. MBC practice principles can help promote patient‐centred care in OUD, personalized addiction therapeutics and facilitate communication of outcomes.